METODE DAN STRATEGI DAKWAH MUHAMMADIYAH DI KABUPATEN DEMAK - Mahfudlah Fajrie (An-Nida : Jurnal Komunikasi Islam, 2014)
Abstract Since the Muhammadiyah proselytizing reform era in Demak began to receive positive response. To improve the proselytizing activities, it needed strategy, management and good proselytizing management in order to make it succeed and the message was received by the public. The purpose of this study was to determine the methods and strategies of Muhammadiyah proselytizing in Demak in 2006-2011. This study used a qualitative approach which the data collection methods were observation, interview and documentation. Data analysis in this study used descriptive qualitative method by using sociological approach technique. Based on the results of the study, it showed that the method of Muhammadiyah proselytizing in Demak included bi al-ḥikmah (way of wisdom), al-mau??i?ah al-ḥasanah (giving good advice) and al-mujādalah bi al-latī hiya aḥsan (having good dialogue). Muhammadiyah proselytizing strategies in Demak was to promote the Islamic teaching in accordance with the shari'ah, established guidance foundation of Hajj rituals, built a dialogue culture and youth coaching, mass media proselytizing, cultural and empowerment proselytizing of the people in the fields of education, economics, social and health. Keywords: Methods, Strategies, Proselytizing, Muhammadiyah Sejak era reformasi dakwah Muhammadiyah di Kabupaten Demak mulai mendapat tanggapan positif, untuk meningkatkan kegiatan dakwah maka perlu adanya strategi, manajemen dan pengelolaan dakwah dengan baik, agar dakwahnya berhasil dan pesan yang disampaikan diterima oleh masyarakat. Tujuan penelitian ini untuk mengetahui metode dan strategi dakwah Muhammadiyah di Kabupaten Demak periode 2006-2011. Penelitian kualitatif dengan metode pengumpulan data melalui observasi, wawancara dan dokumentasi. Analisis data dalam penelitian ini menggunakan metode deskriptif kualitatif dengan teknik pendekatan sosiologis. Berdasarkan hasil penelitian menunjukkan bahwa metode dakwah Muhammadiyah di Kabupaten Demak meliputi metode dakwah bi al-ḥikmah (cara hikmah), al-mau??i?ah al-ḥasanah (nasehat yang baik) dan al-mujādalah bi al-latī hiya aḥsan (berdialog dengan baik). Strategi dakwah Muhammadiyah di Kabupaten Demak yaitu dengan mengedepankan ajaran Islam sesuai dengan syari??at, membentuk lembaga bimbingan manasik haji, membangun budaya dialog dan pembinaan generasi muda, dakwah media massa, dakwah kultural dan dakwah pemberdayaan umat di bidang pendidikan, ekonomi, sosial dan kesehatan. Kata kunci: Metode, Strategi, Dakwah, Muhammadiyah